Bangkitnya nasionalisme islam: Peran bahasa dan sastra arab dalam membentuk identitas - Afrianti, Mike (Maliki Interdisciplinary Journal, 2025)
The rise of Islamic nationalism is a process that involves many aspects, from spiritual, cultural, to political aspects. In this journey, Arabic language and literature play an important role as a symbol of the identity of Muslims and a link in communication between Muslim countries. Arabic not only functions as a means of speaking, but also reflects the purity of Islamic teachings and the closeness of its values to the lives of the people. Arabic literature, on the other hand, is a medium to convey the spirit of struggle, criticism of colonialism, and a description of the social situation faced by Muslims. This article examines how Arabic language and literature help shape shared awareness, strengthen the bonds of brotherhood of the people, and become a means of liberation from colonial domination. In the present era, Arabic language and literature still have an important place in building Muslim identity amidst global challenges and identity crises. Through a descriptive-qualitative approach, this article highlights the importance of maintaining and reinterpreting the richness of Arabic language and literature as part of the rise of contemporary Islamic nationalism